Possibilities and limits of innovation of didactic strategies in primary classes, in the current social context - Ioniță (Cristea), Anca Elena; Stoichici (Iavorschi), Elena (Technium Social Sciences Journal, 2022)
The present study investigates how digital education and the global pandemic crisis influence the reconstruction of teaching strategies through the lens of the pedagogical concept of educational innovation. We contribute to the debate in the specialized literature that discusses the possibilities and limits of the reconstruction of didactic strategies in primary schools as part of a broad process of innovation in education. Identifying the problems faced by primary school teachers, before and after the Covid moment, as well as outlining teaching strategies based on the solutions proposed by them, is a priority in the process of rebuilding the education system. Also during the pandemic, the two main issues raised by an OECD survey of 59 countries were students’ access to technology and teachers’ ability to find ways to carry out their activities using technology. Data from the Teaching and The International Learning Study (TALIS) show that in many countries, teachers’ skills regarding digitization in educational practice are still limited. Remaking didactic strategies, especially in primary school, is necessary to reduce the gaps faced by the current generation of students, those who are the main beneficiaries of the educational act and those who suffer first when the quality of the educational system decreases.